2016
DOI: 10.1016/j.jsat.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Access to Addiction Pharmacotherapy in Private Health Plans

Abstract: Background An increasing number of medications are available to treat addictions. To understand access to addiction medications, it is essential to consider the role of private health plans. To contain medication expenditures, most U.S. health plans use cost-sharing and administrative controls, which may impact physicians' prescribing and patients' use of addiction medications. This study identified health plan approaches to manage access to and utilization of addiction medications (oral and injectable naltrex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Rates of methadone treatment were low among the privately insured, possibly as a result of methadone not being a covered service. 27 We found that the number of PCPs prescribing buprenorphine in Medicaid increased as did the number of people receiving buprenorphine from PCPs. This finding presents compelling evidence that PCP involvement in OUD care is increasing, though it remains concentrated in a relatively small number of providers.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Rates of methadone treatment were low among the privately insured, possibly as a result of methadone not being a covered service. 27 We found that the number of PCPs prescribing buprenorphine in Medicaid increased as did the number of people receiving buprenorphine from PCPs. This finding presents compelling evidence that PCP involvement in OUD care is increasing, though it remains concentrated in a relatively small number of providers.…”
Section: Discussionmentioning
confidence: 68%
“…MOUD initiation rates were slightly higher among Medicaid enrollees compared to privately insured individuals. Rates of methadone treatment were low among the privately insured, possibly as a result of methadone not being a covered service 27 …”
Section: Discussionmentioning
confidence: 98%
“…Previous research has documented that many state Medicaid programs and large private health plans place restrictions on coverage of OUD medications. 14,15 Likewise, while changes in provider guidelines and education, dosing regulations and other policies have been associated with reductions in opioid prescribing for pain, 6 insurance coverage restrictions such as prior authorization (PA) (i.e., enrollee must obtain plan approval before coverage is granted) or step therapy (ST) (i.e., enrollees must document prior trial of a lower-cost medication before receiving coverage for a higher-cost medication) could also be tools used by insurers to limit access to opioids.…”
Section: Introductionmentioning
confidence: 99%
“…Given the high rate of relapse for people with OUDs, medications such as methadone, buprenorphine, and extended-release naltrexone are considered front-line treatment and have been shown to be both effective and cost-effective (American Society of Addiction Medicine 2015; Fullerton et al 2014; Gastfriend 2011; Mattick et al 2014; Reif et al 2016; Schackman et al 2012; Thomas et al 2014). Methadone has been available for decades, yet for treatment of OUDs is only available in “opioid treatment programs” (OTPs) subject to specific federal regulations regarding the dispensing of opioid agonist medications.…”
Section: Introductionmentioning
confidence: 99%